Nanofiber Polymers for Coating Titanium-Based Biomedical Implants - Nthabiseng Nhlapo (Fibers, 2022)
The excellent combination of properties has seen a steep increase in the demand for titanium (Ti)-based material as biomedical implant devices. However, some features that promote biocompatibility are found to be lacking in Ti implants. The use of polymer nanofiber (NF) coating on the surfaces of the implants has been proven to remedy these setbacks. In particular, electrospun NFs are versatile as natural extracellular matrix mimics and as facilitators in the biocompatibility function of Ti-based implants. Therefore, various properties of Ti implants coated with polymer NFs and the correlations among these properties are explored in this review. Synthetic polymers are favorable in tissue engineering applications because they are biocompatible and have low toxicity and degradation rates. Several approved synthetic polymers and polymer hybrids have been electrospun onto Ti implant surfaces to successfully improve the biomedical applicability of the implants with regard to their physical (including diameter and porosity), chemical (including corrosion resistance), mechanical (including elastic modulus, strength and ductility) and biological properties (including tissue integration, antimicrobial and cytotoxicity).